Geological Structure Control on the Formation of Metal Mineralization at Quartz Veins in Jendi Village, Wonogiri Regency, Central Java - Widagdo, Asmoro; Sukadana, I Gde; Indrastomo, Frederikus Dian (EKSPLORIUM, 2022)
Quartz veins in the Jendi area and its surroundings are formed by geological structures with distributions and patterns that need to be known. This study uses data on striation, quartz vein orientation, and metal content in quartz veins. The use of this data aims to determine the relationship between the vein direction pattern and its metal mineral content with the main structure that forms it. The results of this study can be useful in determining the structural model and distribution of veins in the study area. The research method was carried out through a series of field and laboratory work. Fieldwork includes measuring striation data, measuring the orientation of quartz veins, and taking quartz vein samples. Studio work includes stereographic analysis of striation data, rosette diagram analysis of vein measurement data, and analysis of metallic element content of quartz veins. The quartz vein mineralization zone in the study area is controlled by a right slip fault with a northwest-southeast trend that forms a transtension zone with a north-south trend. The north-south trending veins are generally thick, long/continuous, and have a high metal content.